2008
DOI: 10.1080/02844310701318262
|View full text |Cite
|
Sign up to set email alerts
|

Congenital lateral cleft palate and lateral palatal synechiae

Abstract: We report a sporadic case of congenital lateral cleft palate and lateral palatal synechiae and suggest that its mechanism is embryonal. This is the first published case that we know of with cleft palate-lateral synechiae syndrome including the lateral cleft palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Lateral synechia associated with a cleft palate was a rare condition in a patient whom we have treated and followed for 10 years. He did not experience swallowing or speech Preus et al (1974) CPLSS without LS 0 0 No synechia Dinardo et al (1989) CPLSS 0 1 Nakata et al (1993) CPLSS 2 0 Untreated until 8 and 7 years old Cronin et al (2001) CPLSS 0 1 Jaeger et al 2003CPLSS 0 2 Isik et al (2008) CPLSS 1 0 Lateral cleft palate Donepudi et al (2009) CPLSS 2 0 Sybil and Sagtani 2013 impairments but had maxillary hypoplasia. In the literature review, we found only limited long-term pathological information about LS or CPLSS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lateral synechia associated with a cleft palate was a rare condition in a patient whom we have treated and followed for 10 years. He did not experience swallowing or speech Preus et al (1974) CPLSS without LS 0 0 No synechia Dinardo et al (1989) CPLSS 0 1 Nakata et al (1993) CPLSS 2 0 Untreated until 8 and 7 years old Cronin et al (2001) CPLSS 0 1 Jaeger et al 2003CPLSS 0 2 Isik et al (2008) CPLSS 1 0 Lateral cleft palate Donepudi et al (2009) CPLSS 2 0 Sybil and Sagtani 2013 impairments but had maxillary hypoplasia. In the literature review, we found only limited long-term pathological information about LS or CPLSS.…”
Section: Resultsmentioning
confidence: 99%
“…In our literature search, there were 17 cases of CPLSS in 11 reports (Fuhrmann et al, 1972;Preus et al, 1974;Dinardo et al, 1989;Nakata et al, 1993;Cronin et al, 2001;Jaeger et al, 2003;Isik et al, 2008;Donepudi et al, 2009;Sybil and Sagtani, 2013;AbdollahiFakhim et al, 2014;Mascarella et al, 2015; Table 1). Although 12 of these cases were associated with lateral palatal synechiae (Fuhrmann et al, 1972;Nakata et al, 1993;Akpata et al, 1995;Isik et al, 2008;Donepudi et al, 2009;Sybil and Sagtani, 2013;AbdollahiFakhim et al, 2014), the other cases were associated with bilateral AS, except for one case of CPLSS without lateral palatal synechiae (Preus et al, 1974). Conversely, a patient with LS was reported to have a cleft palate and congenital synechia syndrome (Akpata et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Erdogan et al provided the first report of LCP 3. Then, Isik et al presented a case of lateral palatal synechia with LCP 4. In the same study, it was suggested that the lateral palatal synechia, which is a residue of the buccopharyngeal membrane, might cause LCP by preventing the anterior movement of the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…Only three lateral CP (LCP) cases have been presented in the literature, and no aetiological factors have been detected in these cases 3–5. We aimed to present a unique case of unilateral CFM and LCP.…”
Section: Introductionmentioning
confidence: 99%